"Are there Racists in Yugoslavia?" Debating Racism and Anti-blackness in Socialist Yugoslavia. Issue 2 (2022) - Wright, Peter
Abstract : This article examines debates, scholarly studies, and literary representations of the phenomenon of racism in socialist Yugoslavia and Yugoslavs' relationship to whiteness in the 1960s and 70s. I argue that the persistent activism of black African students helped provoke official, scholarly, and public discussions about the thorny question of racism in Yugoslav society during this time. The salience of black students' accusations eventually made something that was taboo in the 1950s and early 1960s—namely, entertaining the prospect that anti-black racial prejudice existed in non-aligned, socialist, and anti-racist Yugoslavia—into an active subject of debate by the end of the decade. Importantly, the relative candidness with which academic studies and popular literature addressed racism indicates a reflexivity about "racial" questions on the part of socialist Yugoslav society, something that scholarship has largely neglected in favor of focusing on the suppression or elision of race and the inadequacy of state socialist responses to the problem of domestic expressions of prejudice.